Mechanically Robust Irradiation, Atomic Oxygen, and Static-Durable CrO x /CuNi Coatings on Kapton Serving as Space Station Solar Cell Arrays - Zhang, Yifan; Li, Qian; Yuan, Heng; Yan, Weiqing; Chen, Shunian; Qiu, Menglin; Liao, Bin; Chen, Lin; Ouyang, Xiao; Zhang, Xu; Ying, Minju (ACS applied materials & interfaces, 2022)
The polymers that served for solar cell arrays are constantly subject to various hazards, such as atomic oxygen (AO), ion irradiation, or electrostatic discharge (ESD) events. To address these issues, we fabricated and sifted CrO0.16/CuNi-coated Kapton with a gradient structure with the goal of reaching an equilibrium between AO durability and resistance. The resulting material exhibits an impressively low E y of 6.61 × 10–26 cm3 atom–1, 2.20% of which was detected as pristine Kapton. Self-evolution of the CrO0.16 coating under 525.4 displacement per atom (dpa) Fe+ ion irradiation indicated that it can still maintain a good state of ultrafine nanocrystalline in addition to local amorphization. Its AO-based degradation and irradiation evolution are demonstrated by molecular dynamics (MD) simulations. It is mechanically robust enough to endure the cyclic folding treatments attributed to its gradient structure fabrication. Moreover, the CrO0.16/CuNi-coated Kapton exhibits alleviated electrostatic accumulation capability and sufficient conductivity. Our strategy has promising potential for creating surface protection on flexible polymers operating in the low Earth orbit (LEO).